2015
DOI: 10.1186/s13045-015-0129-1
|View full text |Cite
|
Sign up to set email alerts
|

Competing endogenous RNA networks: tying the essential knots for cancer biology and therapeutics

Abstract: A recently discovered dimension of post-transcriptional gene regulation involves co-regulatory crosstalk between RNA transcripts, which compete for common pools of microRNA (miRNA) molecules. These competing endogenous RNAs (ceRNAs), or natural miRNA sponges, have an active role in regulating miRNA availability within the cell and form intertwined regulatory networks. Recent reports have implicated diverse RNA species including protein-coding messenger RNAs and non-coding RNAs as ceRNAs in human development an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
149
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(153 citation statements)
references
References 79 publications
4
149
0
Order By: Relevance
“…Previous studies showed that both H19 and HULC are similar to ceRNAs [38] in human embryonic kidney cells and human embryonal carcinoma cells by sponging let-7 and miR-372, respectively [27, 39]. To determine whether H19 and HULC have similar roles in CCA, we focused on the potential functions of the let-7 and miR-372 families in CCA cells (Additional file 1: Figure S4A).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that both H19 and HULC are similar to ceRNAs [38] in human embryonic kidney cells and human embryonal carcinoma cells by sponging let-7 and miR-372, respectively [27, 39]. To determine whether H19 and HULC have similar roles in CCA, we focused on the potential functions of the let-7 and miR-372 families in CCA cells (Additional file 1: Figure S4A).…”
Section: Resultsmentioning
confidence: 99%
“…In a ceRNA model, lncRNA release or upregulate target mRNA of miRNAs by competitively binding with the same miRNAs Zhang et al [27][28][29][30][31]. TUG1 participates in the progression and development of multiple tumors by acting as a ceRNA Zhang et al [22,24,26,[32][33][34][35][36].…”
Section: Tug1 Regulates Zeb1 By Competitively Binding With Mir-142-3pmentioning
confidence: 99%
“…MicroRNAs (miRNAs) comprise a class of small noncoding RNAs implicated in post-transcriptional RNA regulation. These RNA molecules are ~22 nt in length (9). By binding to complementary sequences in the 3'UTRs of targeted mRNAs, miRNAs degrade or inhibit their translation and regulate a range of cellular functions such as differentiation, proliferation, apoptosis and migration of tumor cells (10).…”
Section: Introductionmentioning
confidence: 99%